The origin, development and modern application of the law relating to marital rape: a comparative legal appraisal - Mohamad Yunus, Mohamad Ismail (The Malaysian Current Law Journal Sdn Bhd, 2005)
"Marital rape" is defined as sexual intercourse by the husband with his wife without her express consent. The husband and wife must be legally married and recognised a s a married couple, having the same rights and obligations under the law. Under the definition of rape that is generally used by the courts, it is "an act of sexual intercourse by the male with a woman other than his wife". Under this commonly accepted definition, it is not legally possible for the husband to rape his own wife. The husband cannot be liable as the principal offender based on the fact that consent to marriage is also consent to sexual intercourse so long as the marriage subsists. On the other hand, it is also observed that many women who have been sexually assaulted by their husbands do not treat themselves as having been raped. They tend to view the assault as part of marital conflict for which they are to blame, wondering if their own inadequacies as wives and partners are the root cause of the problem and believing that they are the ones who provoked their husbands. Further, the husband's behaviour in becoming violent is taken by many to be a judgment on them. It is also stated that marital rape is part of a personal shame that the victims do not want others to know. By formally exempting such behaviour from criminal prosecution, this, in effect, appears to be a private affair between spouses and not a matter of concern to society. Thus, this article attempts to set out the law relating to marital rape apart from highlighting the historical basis and contemporary arguments in favour of spousal immunity. However, it is suggested that the immunity, if inconsistent with the status of woman today, ought to be abolished or, at least, substantially modified.